SPEECH OF THREE YEARS OLD CHILDREN IN LANGUAGE ACQUISITION - Safira, Ayu Dian; Sagala, Rakhmat Wahyudin (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
This study discusses Speech of Three Years Old Children in Language Acquisition. The purpose of this study is to find out that three-year-old children in the pronunciation of vowels and consonants of words or sentences are still less precise and unclear, to find out why three- years old children cannot compose perfect sentences in conversation. A qualitative descriptive method was applied to analyze the data. The data of this study were taken from the of three- years old children speech, namely DSZ and SYF. The results obtained indicated that the research subjects were able to produce sentences according to their function as a communicative functions, namely declarative sentences, interrogative sentences, and command sentences. Some were influenced by cognitive factors, social background, and input to improve communication and language development. So that the research subjects can master the language and communicate well